Pengaruh kompensasi terhadap kepuasan kerja karyawan pada PT. Sumber Hijau Permai (SHP) Jambi - Oktaviani, Izmi Anisa; Jaya, Indra; Willian, Rohman (Jurnal Dinamika Manajemen, 2022)
This study aims to obtain an overview of employees’ compensation and job satisfaction at the PT. Sumber Hijau Permai (SHP) Jambi. Furthermore, to explain the effect of payment on employee job satisfaction. The study population was employees at the PT. Sumber Hijau Permai (SHP) Jambi totaling 87 people. The sampling method uses the census method, meaning that all present population was sampled. Based on the research objectives, the type of research is explanatory research (explanatory research) done to explain the causal relationship between research variables through hypothesis testing. The hypothesis is tested using a simple linear regression equation using SPSS 17.0 for Windows. Descriptive results of this study indicate that the compensation received by employees is categorized as entirely reasonable and employee satisfaction in the work. Employees feel pretty satisfied in his job. Furthermore, the magnitude role or contribution of variable compensation can explain the variable job satisfaction of employees is 56,2%. At the same time, the remaining 43,8% is influenced by other factors which are not disclosed in this study.